2009
DOI: 10.1016/j.jana.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Stigma Reported by People Living With HIV in South Central China

Abstract: This cross-sectional study described the level of stigma reported by people living with HIV (PLWH) in south central China and identified factors associated with the individuals' perceptions of stigma. The authors carried out face-to-face interviews among 322 PLWH. Over half (51%) reported experiencing stigma, 78% reported feelings of negative self-worth, 75% reported interpersonal insecurity, 84% experienced financial problems, and 58% worried about disclosure of their disease. High levels of self-perceived st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 15 publications
3
29
0
1
Order By: Relevance
“…Several other studies have shown that the HIV transmission route influences perceived stigma [10,11]. The present study showed a marked difference between individuals infected with HIV by commercial plasma donors and those infected by other routes.…”
Section: Discussionsupporting
confidence: 52%
“…Several other studies have shown that the HIV transmission route influences perceived stigma [10,11]. The present study showed a marked difference between individuals infected with HIV by commercial plasma donors and those infected by other routes.…”
Section: Discussionsupporting
confidence: 52%
“…It could also be because of culturally relevant moral judgments about the modes of disease transmission and high-risk groups. In particular, socially marginalized people living in remote areas are most likely to be stigmatized (Chan, Yang, Zhang, & Reidpath, 2007;Hong et al, 2008;Li, Wang, Williams, & He, 2009). Stigma has also led to fewer social resources being available to HIV-infected people in China Zhou, 2009).…”
Section: Hiv Care System In Chinamentioning
confidence: 99%
“…In this way, PLWHA can avoid being discriminated against by medical personnel so that they can be treated properly. Meanwhile, several other studies have shown that the HIV infection route influenced perceived discrimination (Li et al 2009;Brener et al 2013). A possible explanation for this situation could be that individuals with sexual transmission usually had a chaotic sex life that was contrary to a normal dating relationship, and they may be more afraid of the reception that their illness may receive from family members and especially from their spouses.…”
Section: Discussionmentioning
confidence: 99%